2019
DOI: 10.3892/etm.2019.7492
|View full text |Cite
|
Sign up to set email alerts
|

Application value of procalcitonin, C‑reactive protein and interleukin‑6 in the evaluation of traumatic shock

Abstract: Procalcitonin (PCT), C-reactive protein (CRP) and interleukin-6 (IL-6) were detected to explore the value of these inflammatory markers in the assessment of traumatic shock patients. The clinical data of 80 patients with traumatic shock and infections in Zhangzhou Municipal Hospital of Fujian Province from January 2014 to December 2017 were collected as the experimental group. During the same period, 80 acute trauma patients who did not suffer from traumatic shock were regarded as the control group. According … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…The second elevation of serum PCT levels within 3 to 7 days post-injury can be attributed to opportunistic bacterial infections and sepsis due to a compromised immune system and early CARS and PICS in severe trauma. Infection-induced SIRS, CARS, and PICS have stronger correlations with poor prognostic outcomes of trauma compared to trauma-induced types (38,54,55). These results have been observed in both survivor and non-survivors cases following traumatic injuries, respectively (56).…”
Section: Pctmentioning
confidence: 92%
See 2 more Smart Citations
“…The second elevation of serum PCT levels within 3 to 7 days post-injury can be attributed to opportunistic bacterial infections and sepsis due to a compromised immune system and early CARS and PICS in severe trauma. Infection-induced SIRS, CARS, and PICS have stronger correlations with poor prognostic outcomes of trauma compared to trauma-induced types (38,54,55). These results have been observed in both survivor and non-survivors cases following traumatic injuries, respectively (56).…”
Section: Pctmentioning
confidence: 92%
“…It typically increases within 6-12 hours, reaching a peak after 24-72 hours (37). This increase is on days 1 to 3 after admission, which continues for the following days, and is associated with poor outcomes (38). Whereas a decrease in this protein after a temporary increase at the time of admission is correlated with good prognosis (38).…”
Section: Crpmentioning
confidence: 99%
See 1 more Smart Citation
“…CRP is an acute-phase protein synthesized in the liver [141], which is closely related to inflammation, infection, and tissue damage, and CRP levels are not influenced by age, gender, and physical condition [142]. Clinical studies have shown that CRP plays a crucial role in monitoring the inflammatory process and infection [143].…”
Section: Discussionmentioning
confidence: 99%
“…There were differences in serum PCT, CRP, and IL-6 between the good prognosis and the poor prognosis group at the time of T1–T4 ( p < 0.05). The expression levels of PCT, CRP, and IL-6 in the serum of patients with poor prognosis were higher than those with good prognosis ( p < 0.05) [ 71 ].…”
Section: Methodsmentioning
confidence: 99%